Using sandwich composite shells for fully pressurized tanks on liquefied petroleum gas carriers - Alankaya, Veysel (Strojniški vestnik, 2016)
The growth of shipping as the main link of the seaborne gas supply chain results from the growing demand for liquefied petroleum gasses due to their various uses, such as fuel for cooking/heating, automotive power, and numerous applications. This study investigates the structural suitability of sandwich composite materials for pressurized tanks, which can be used in on-board carriers or barges for transportation, as well as inland for industrial or residential storage needs. The analytical solution methodology for analysing stresses and deformations is based on higher order shear deformation theory (HSDT). A boundary discontinuous generalized double Fourier series approach is used to solve highly coupled linear partial differential equations. The complementary boundary constraints are introduced through boundary discontinuities, generated by the selected boundary conditions for the derivation of the complementary solution. Numerical solutions are presented for laminated sandwich shells having both cylindrical and spherical forms, which are the preferred geometries for pressurized tanks.
Keywords: analiza po metodi končnih elementov; dvakrat ukrivljena lupina; mejna nezveznost; sendvič kompoziti; tankerji za ukapljen naftni plin; teorija strižnih deformacij višjega reda; tlačne posode